Difficulties In Teaching Writing Descriptive Text - Al Zahrah, Madina; Erlina, Dian; Dwi Amrina , Rizqy (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
When writing the descriptive text, the teachers found difficulties during the teaching process. This study aimed to determine teachers’ difficulties in teaching and writing descriptive texts. The participants were English teachers at SMP Negeri 2 Palembang who taught seventh graders using total sampling. This study used a qualitative method. Interviews were used to collect the data. The data obtained from the interviews were analyzed using thematic analysis. The result of this study showed that (1) difficulties came from teachers themselves, such as difficulty in designing lesson plans and difficulty in utilizing learning media, (2) difficulties came from students, consisting of a lack of understanding about the generic structure of descriptive text, lack of understanding about mechanical aspect of writing, lack of grammar knowledge, and lack of about vocabularies knowledge, (3) difficulties came from learning environment, consists of difficult to control the large class and limited teaching time in the class